STRATEGI KOMUNIKASI PEMASARAN DINAS PARIWISATA PEMUDA DAN OLAHRAGA DALAM MEMPROMOSIKAN WISATA KULINER SAGU DIKABUPATEN KEPULAUAN MERANTI - Atia, Nurul; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Culinary became one of the attractions of tourist while visiting somewhere. The district Kepulauan Meranti is now as sagoculinary tour. Varius sago-based food prepations can be found in the district. In this case, Dinas Pariwisata Pemuda anD Olahraga with the incessant promotion of sago food prepations as a typical culinary tour of district Kepulauan Meranti. in promoting sago tourism culinary required affective marketing communication strategy to create attraction. The purpose of this research is to knoe the marketing communicatoan strategy from Dinas Pariwisata Pemuda and Olahraga through Advertising,Personal Selling, Direct Marketing and Publicity in promoting sago culinary tourism in the district Kepulauan Meranti.This study use a qualitative method. Subject in thi study consisted of nine people with informants through techinique purposive sampling.data collection techniques are divided into three part, namely interview, observations, and documentation. Data analysis techniques in thi study using data Miles dan Hiberman. Checking the validity of data using optical elongation and triangulation techniques.The results show that marketing communications strategy is done by Dinas Pariwisata Pemuda and Olahraga in promoting sago culinary touris through print media advertising is newspaper and banner, electronic media radio. Through personal selling is event and gedung promosi, through direct marketing that is instagram. And through publicity by means of media covering event and published by the media at no charge and implied message typical culinary sago promotions of district Kepulauan Meranti.